2008
DOI: 10.4103/0972-0707.45249
|View full text |Cite
|
Sign up to set email alerts
|

The influence of different composite placement techniques on microleakage in preparations with high C- factor: Anin vitrostudy

Abstract: Objective:This study evaluated the marginal leakage around class-I cavity preparations restored with Nanofilled composite (Filtek Z-350 A2 shade, 3M ESPE, USA) and a self-etch adhesive (Xeno III, DENTSPLY/Caulk) using different composite placement techniques.Materials and Methods:Standardized class-I cavities were prepared on 36 caries-free, extracted human premolars and were randomly assigned to three groups: (1) Horizontal incremental curing was done; each increment of thickness 1.5 mm was cured one after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…The second layer in the oblique technique, which was also a diagonal layer, was not able to cover the first diagonal layer in the cervical area, which did occur with the second layer of the centripetal build up technique (15). Duarte S et al (2008) (10) reported that polymerization shrinkage was less in the centripetal technique compared to oblique incremental technique. Though the results of these two techniques of composite placement were statistically insignificant but centripetal technique showed less microleakage then the oblique increment, probably because the number of increments used were more with centripetal technique (5 increments) than oblique techniques (4 increments).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second layer in the oblique technique, which was also a diagonal layer, was not able to cover the first diagonal layer in the cervical area, which did occur with the second layer of the centripetal build up technique (15). Duarte S et al (2008) (10) reported that polymerization shrinkage was less in the centripetal technique compared to oblique incremental technique. Though the results of these two techniques of composite placement were statistically insignificant but centripetal technique showed less microleakage then the oblique increment, probably because the number of increments used were more with centripetal technique (5 increments) than oblique techniques (4 increments).…”
Section: Discussionmentioning
confidence: 99%
“…Control of polymerization shrinkage stresses during a direct composite resin restoration is important for achieving a perfect adaptation between restoration and cavity wall. In order of importance, the factors involved in shrinkage stresses are cavity C-factor, cavity size, incremental technique, intensity and position of curing light, and properties of composite (10). In this study, attempts were made to keep all these variables constant, except for the composite placement technique.…”
Section: Discussionmentioning
confidence: 99%
“…Santhosh et al investigated whether the modification of the horizontal incremental method was beneficial in terms of C-factor, which is effective for polymerization shrinkage stress and therefore microleakage (25). Three different methods -the classical horizontal incremental technique (gingivoocclusal), concave surface formation and split technique -were compared in Class I cavities with a high C-factor and no statistical difference was found between methods in terms of microleakage.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, microleakage associated with polymerization shrinkage is a major drawback of resin composites, since the resulting shrinkage stress can cause microgap formation at the resin-enamel interface. Indeed, microleakage is one of the most cited reasons for failure of composite resin restorations (Dickinson & Leinfelder, 1993;Davidson & Feilzer, 1997;Santhosh et al, 2008). The shrinkage stresses generated during polymerization can lead to loss of marginal adaptation, resulting in adhesion failure and microgap formation.…”
Section: Introductionmentioning
confidence: 99%